2008
DOI: 10.1007/s00380-008-1058-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of breast arterial calcification and carotid intima-media thickness

Abstract: Breast arterial calcification (BAC) on mammography has been identified as calcific medial sclerosis of medium-sized breast arteries, and has been reported to be associated with cardiovascular risk factors, coronary artery disease, and cardiovascular mortality. Carotid intima-media thickness (C-IMT) is a well-known surrogate marker of atherosclerosis and predictor of cardiovascular morbidity and mortality. Consequently, the present study was designed to investigate the association between the presence of BAC on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
1
12
1
2
Order By: Relevance
“…This study showed an association between carotid plaque and BAC, although the association between BAC and IMT was stronger. Yildiz et al 29 conducted a similar study and reported mean CIMT of 0.87 ± 0.17 in BAC-positive women compared with 0.60 ± 0.19 in BAC-negative women with a coefficient of 0.463 ( P < 0.001). However, Sarrafzadegann et al, 16 who included only premenopausal women referred for coronary angiography, failed to show any statistically significant relation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This study showed an association between carotid plaque and BAC, although the association between BAC and IMT was stronger. Yildiz et al 29 conducted a similar study and reported mean CIMT of 0.87 ± 0.17 in BAC-positive women compared with 0.60 ± 0.19 in BAC-negative women with a coefficient of 0.463 ( P < 0.001). However, Sarrafzadegann et al, 16 who included only premenopausal women referred for coronary angiography, failed to show any statistically significant relation.…”
Section: Discussionmentioning
confidence: 83%
“…The study period ranged from 1995 to 2011, and the studies looked at relation between BAC and CVD, cardiovascular (CV) mortality, coronary, cerebral or systemic atherosclerosis, CIMT, and coronary calcium. We found 19 studies 725 looking at the association of BAC and CAD and/or CVD, 8 studies between BAC and stroke, 79,20,21,23,24,26 2 studies between BAC and PAD, 27,28 3 studies between BAC and CIMT, 16,19,29 and 2 studies between BAC and coronary artery calcification (CAC). 30,31 Tables 1 and 2 show detailed information regarding individual studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although BAC is typically considered a benign finding unrelated to breast cancer risk/mortality, previous studies have suggested that BAC on screening mammography is associated with the presence of hypertension, diabetes mellitus, angiographically defined coronary artery disease, and increased cardiovascular mortality. 9 Potentially, BAC calcification on screening mammography may identify breast cancer patients at higher cardiovascular risk following breast RT for which more aggressive cardiac sparing and aggressive cardiac risk reduction may be warranted. 10 Thus, we aimed to evaluate the impact of more modern breast RT on late cardiac events and further hypothesize that BAC on screening mammography may predict for patients at higher risk for cardiovascular events following breast RT.…”
Section: Introductionmentioning
confidence: 99%
“…Intimal changes may reflect cardiovascular and neurovascular diseases. While a number of studies analyzed the correlation between cardiovascular disease and BAC, studies on the association of BAC and carotid plaque are very rare (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%